A call to improve sampling methodology and reporting in young novice driver research. Issue 1 (27th July 2016) - Scott-Parker, B; Senserrick, T
Abstract : Young drivers continue to be over-represented in road crash fatalities despite a multitude of research, communication and intervention. Evidence-based improvement depends to a great extent upon research methodology quality and its reporting, with known limitations in the peer-review process. The aim of the current research was to review the scope of research methodologies applied in 'young driver' and 'teen driver' research and their reporting in four peer-review journals in the field between January 2006 and December 2013. In total, 806 articles were identified and assessed. Reporting omissions included participant gender (11% of papers), response rates (49%), retention rates (39%) and information regarding incentives (44%). Greater breadth and specific improvements in study designs and reporting are thereby identified as a means to further advance the field.